Split objects : A disciplined use of delegation within objects - Bardou, Daniel; Dony, Christophe (1996)
This paper’s primary aim is to improve the understanding of the delegation mechanism as defined in [18]. We propose a new characterization of delegation based on the notions of name sharing, property sharing and value sharing. It allows us (1) to clearly differentiate delegation from classinheritance in particular and more generally from other inheritance mechanisms and (2) to explain how a founded use of delegation relies on a correct semantics of variable property sharing between objects connected by a delegation link. We then describe a model of split objects which is proposed as an example of a disciplined and semantically founded use of delegation, where property sharing expresses viewpoints within objects.
Formato de archivo: PDF. -- Disponible también en línea (Cons. 20/04/2009)
ACM SIGPLAN Notices 1996 31(10) : 122 - 137.
Keywords: PROGRAMACIÓN ORIENTADA A OBJETOS; LÓGICA Y SIGNIFICADO DE LOS PROGRAMAS